A Behavioral Genetic Analysis of Alexithymia and the Dark Triad Traits of Personality. (8th April 2013) - Cairncross, Molly; Veselka, Livia; Schermer, Julie Aitken; Vernon, Philip A.
Abstract : The present study is the first to assess phenotypic correlations between alexithymia and the Dark Triad traits of personality in a community sample, as well as the common genetic and environmental factors underlying these correlations. Participants were 232 North American adult twin pairs who completed the Narcissistic Personality Inventory, the Self-Report Psychopathy Scale, the MACH-IV, and the Toronto Alexithymia Scale. Results revealed that alexithymia correlates significantly and positively with psychopathy and Machiavellianism, and negatively with narcissism. Subsequent bivariate behavioral genetic analysis demonstrated that these phenotypic correlations were primarily attributable to common genetic and common non-shared environmental factors. The implication of these findings regarding the maladaptive functions of alexithymia within the antisocial realm of behavior and the need for replication are discussed.